Foreign language anxiety in and outside the classroom: A case of a non-native speaking student living abroad - Nastiti, Reni (LingTera, 2023)
Speaking in a foreign language, which is often perceived as intimidating by many foreign language learners, has long been associated with foreign language anxiety (FLA), particularly foreign language speaking anxiety (FLSA).  Although numerous studies have investigated FLA and FLSA, most have focused on the classroom environment, whereas the settings outside the classroom, where learners use the language to communicate with native speakers and foreigners, have been relatively overlooked. Although a foreign language classroom environment can be a significant source of anxiety, an authentic target language environment could also trigger anxiety. This study aims to address this gap by investigating FLA and FLSA in both classroom and non-classroom settings from the perspective of a Turkish student living in London. Unlike traditional questionnaire-based quantitative methods used in previous research, this study employs a qualitative method to better understand these issues from the participant's lived experience in both settings. The interview data revealed that the participant experienced a higher degree of anxiety outside the classroom, with peers having a greater impact on her degree of speaking anxiety than teachers in the classroom.